A comparative study of biodiesel in Brazil and Argentina: An integrated systems of innovation perspective. (March 2022) - Nikas, A.; Koasidis, K.; Köberle, A.C.; Kourtesi, G.; Doukas, H.
Abstract: Transport is among the sectors highly dependent on fossil fuels, relying almost exclusively on petroleum products. Biofuels have been suggested as a technology contributing to the sector's decarbonisation, especially in sub-sectors where upscaling electrification innovation is challenging. Brazil and Argentina have long been top biofuel producers. This research employs an integrated innovation systems framework to study the historical evolution of the dominant regime in the two countries' transportation and the recent emergence of the biodiesel technological system to provide insights and policy implications for future trajectories and decarbonisation strategies. Our analysis highlights that landscape pressures have provided windows of opportunity for technological change, with Brazil following a more sustainable pathway based on ethanol as an alternative fuel, which allowed the country to later build on cumulative knowledge and lessons transferred from the passenger vehicle sector to freight, while Argentina has locked-into a natural gas-based innovation path. It also discusses that, with the recent expansion of the biodiesel industry, a key challenge for Brazil lies in keeping up the pace and unlocking the potential after reaching the 10% mandate amid concerns over food security and the lack of diversified feedstock, and for Argentina in balancing its biodiesel exports and domestic consumption. Highlights: An integrated Systems of Innovation framework is applied to Brazil and Argentina. Transport is analysed from a multi-level perspective, then biodiesel from a TIS lens. Brazil's innovation was driven by ethanol and biodiesel; Argentina's locked into gas. A key challenge for Argentina lies in balancing biodiesel exports and domestic use. Brazil must instead focus on unlocking the potential after reaching the 10% mandate.